A Computational Investigation on Structural, Mechanical, Electronic, Magnetic, Thermoelectric, and Optical Properties of CrXPb (X = Sc, Ti) Half-Heusler Alloys - Dey, Aditya; Sharma, Ramesh; Dar, Sajad Ahmed; Raza, Hafiz Hamid (Journal of superconductivity and novel magnetism, 2021)
We have performed a broad computational study of two half-Heusler (HH) alloys CrXPb (X = Sc, Ti) by systematically investigating their structural, mechanical, electronic, magnetic, thermoelectric, and optical properties by means of spin polarized ab initio simulations using density functional theory. Their relaxed structures indicated that they attain cubic structure in ground state. We have used PBE-GGA method for optimizations and for attaining the most accurate results of all properties, the mBJ-GGA approach is applied. Both these compounds are ductile in nature and have anisotropic elastic behavior and high stiffness. CrScPb is observed to acquire metallic nature for both spins, whereas CrTiPb is observed to have half-metallic nature (narrow band gap of 0.96 eV) with a magnetic moment of 5 μ B and 4 μ B for CrScPb and CrTiPb respectively. Furthermore, the thermoelectric properties showed that CrScPb has comparable but better quantity of figure of merit (ZT~0.25 for spin-up and ~ 0.5 for spin-down at room temperature) for both spins and CrTiPb has improved response for spin-up, since ZT is close to 1 at room temperature. Such values showed the efficiency of these alloys for energy conversion and power generation. Moreover, the optical properties showed variable and remarkable optical behavior in visible and UV ranges. We observed fascinating optical applications such as energy storage, reshaping of phases in optical antennas and magentaoptical devices. In nutshell, we comprehend the various properties of two potential HH alloys targeting for various applications.